Doping-free circularly polarized electroluminescence of AIE-active chiral binaphthyl-based polymers. Issue 69 (13th August 2018) - Yang, Lan; Zhang, Yu; Zhang, Xueyan; Li, Nengquan; Quan, Yiwu; Cheng, Yixiang
Abstract : AIE-active chiral polymer enantiomers ( S -/ R -P) can emit green circularly polarized electroluminescence (CP-EL) with g EL up to 0.024. Abstract : AIE-active chiral polymer enantiomers ( S -/ R -P) can emit green circularly polarized electroluminescence (CP-EL) with g EL up to 0.024 without alignment layers and chiral dopants, which represents the first example of CP-OLEDs based on AIE-active main-chain chiral polymers.